G193 The train study: transfusion in neonates and ideal red cell volume study, a randomised control trial: isrctn68861901. (12th March 2018) - Elmusharaf Abdelrahman, S; Bahari, M; Mareri, A; Segurado, R; Quigley, J; Culliton, M; Fitzpatrick, J; Paturi, B; Vavasseur, C; Molloy, E
Abstract : Aim: There are different guidelines to calculate red blood cell (RBC) replacement volume in neonates, ranging from 5 ml/kg up to 20 ml/kg RBC volume to be transfused. We aimed to investigate which method is more reliable in achieving the desired Haemoglobin (Hb) from a single blood transfusion in infants<32 weeks gestation admitted to the Neonatal Intensive Care Unit (NICU). Methods: Preterm infants<32 weeks gestations were enrolled if they were admitted to the Neonatal Intensive Care Unit, required a RBC transfusion and parental consent was obtained. Infants were excluded if there was evidence of active bleeding, intraventricular haemorrhage (IVH) grade ≥III or more at the time of transfusion, <24 hours post surgical intervention, ABO/Rh incompatibility or Disseminated Intravascular Coagulopathy. Each infant was then randomised to either the standard practice of calculating RBC volume (RBC volume=20 ml/kg) or to the intervention volume calculation (RBC volume=5×working weight × [Hb desired – Hb current]). Results: Sixty three infants were randomised, 55 infants had values for both the post-transfusion Hb and the target Hb. A chi-square test was used to determine if there was an association between the group to which the infant was randomised and whether they achieved the target Hb level. 21 (84.0%) of the 25 infants in the control group achieved the target Hb level, and 20 (66.7%) of the 30 infants in the intervention group achieved the target Hb level. Testing at a 5% significance level, there is no significant difference between the control and intervention groups in the proportion of infants who achieved the target Hb level (p=0.142, df=1). Conclusion: There was no significant difference between the 2 methods of RBC volume calculation in achieving the target Hb. The simpler calculation method of 20 ml/kg may be the optimum method as less chance of calculation error.